CZT와 NaI 검출기 물질 기반 물리적 변화에 따른 영상의 질 분석에 관한 연구: 몬테카를로 시뮬레이션 - 고혜림; Hye-rim Ko; 유유리; Yu-ri Yoo; 박찬록; Chan-rok Park (한국방사선학회 논문지, 2021)
본 연구의 목적은, 몬테 카를로 시뮬레이션 기반 조준기 길이와 검출기 두께 변화에 따른 Cadimium Zinc Telluride (CZT) 와 NaI 검출기 물질을 변화하면서 영상의 질을 비교 평가 해보고자 한다. CZT 와 NaI 검출기 물질 기반 감마카메라를 각각 모사하였고, 조준기 길이는 1, 2, 3, 4, 5, 6 cm, 검출기 두께는 1, 3, 5, 7mm 로 설정하였다. 1 MBq의 점선원을 이용해 민감도, 4.45, 3.80, 3.15, 2.55 mm 의 지름을 가진 자체 제작한 팬텀을 모사하고, 가장 큰 지름인 4.45 mm 영상에 관심영역을 설정하여 signal to noise ratio (SNR)과 프로파일을 이용하여 각각 획득영상을 분석하였다. 조준기 길이에 따른 CZT 검출기 기반 민감도는 2.3 ~ 48.6 cps/MBq, NaI 검출기 기반 민감도는 1.8 ~ 43.9 cps/MBq 이고, CZT 검출기 기반 팬텀을 활용한 SNR은 3.6 ~ 9.8, NaI 검출기 기반 팬텀 SNR은 2.9~9.5다. 조준기 길이 변화에 따른 프로파일은 조준기의 길이가 증가할수록 영상의 공간 분해능이 향상함을 확인하였다. 또한, 검출기 두께에 따른 CZT 검출기 기반 민감도는 0.04 ~ 0.12 cps/MBq 이고, NaI 검출기 기반 민감도는 0.03 ~ 0.11 cps/MBq 다. CZT 검출기 기반 팬텀 SNR은 7.3~9.8 이며, NaI 검출기 기반 팬텀 SNR은 5.9~9.5다. 또한, 검출기 두께 변화에 따른 프로파일은 검출기 두께가 증가할수록 산란선이 증가함으로써 영상의 공간 분해능이 감소함을 확인하였다. 이 연구데이터를 기반으로 영상 획득 목적에 따라 검출기의 종류와 두께, 조준기의 길이를 선택하여 최고의 영상의 질을 획득할 수 있어야 한다. In this study, we evaluated image quality by changing collimator length and detector thickness using the Geant4 Application for Tomographic Emission (GATE) simulation tool. The gamma camera based on the Cadimium Zinc Telluride (CZT) and NaI detectors is modeled. In addition the images were acquired by setting 1, 2, 3, 4, 5, and 6 cm collimator length and 1, 3, 5, and 7 mm detector thickness using point source and phantom, which is designed by each diameter (4.45, 3.80, 3.15, 2.55 mm) with 447, 382, 317, and 256 Bq. The sensitivity (cps/MBq) for point source, and signal to noise ratio (SNR) and profile for phantom at the 4.45 mm by drwan the region of interests were used for quantitative analysis. Based on the results, the sensitivity according to collimator length is 2.3 ~ 48.6 cps/MBq for CZT detector, and 1.8 ~ 43.9 cps/MBq for NaI detector. The SNR using phantom is 3.6~9.8 for CZT detector, and 2.9~9.5 for NaI detector. As the collimator length is increased, the image resolution is also improved according to profile results based on the CZT and NaI detector. In addition, the senistivity for detector thickness is 0.04 ~ 0.12 cps/MBq for CZT detector, and 0.03 ~ 0.11 cps/MBq. The SNR using phnatom is 7.3~9.8 count for CZT detector, and 5.9~9.5 for NaI detector. As the detector thickness is increased, the image resolution is decreased according to profile results based on the CZT and NaI detector due to scatter ray. In conclusion, we need to set the geometric material such as detector and collimator to acuquire suitable image quality in nuclear medicine.